Efectos de biochar como enmienda edáfica en la calidad sensorial del cacao ccn-51 en el sector de Río Negro - Balladares Orellana, Francisco Josue (Machala : Universidad Técnica de Machala, 2020)
Biochar is a product rich in carbon that is obtained by the decomposition of organic matter through the process of pyrolysis. Biochar generates positive responses when used as an edaphic amendment in agricultural soils, it improves the physicochemical properties of the soil and the physiological behavior of plantas. Biochar promotes crop production and yields and has a positive effect on increasing fruit quality and weight. Ecuador is considered the first producer of fine and aromatic cocoa with 70% of world production, thanks to the eco-geographical conditions of our country that allow the crop to express all its goodness in quality, flavor and aroma. The existence of cocoa dates back 2000 years in Central América, cultivated and produced by civilizations such as the Mayans and Aztecs, although there are archaeological remains of varieties of Theobroma cacao subsp. Cocoa dating back more than 5000 years found in the coastal and Amazon área of Ecuador. Currently, the National type cocoa is in danger of extinction since it is being replaced by other more productive materials, among which the clonal hybrid CCN-51 stands out for its resistance to plagues and diseases and its great productivity. This clone, together with the development of new fermentation techniques, began to be one of the most desired and valued worldwide for its quality and aroma. The main objective of this work was to determine the effect of biochar applied as an edaphic amendment alone and in combination with other edaphic amendments on the sensory quality of CCN-51 cocoa. For this word, the treatments were applied in the plants at random for each block, this was developed in the farm “Don Hermel” belonging to the sector of Río Negro, the doses of the treatments were Biochar 100g+ Chicken Manure 50g (T1), Biochar 100g+ Fossil Shell Agro 5g+ Chicken Manure 50g (T2), Biochar 50g+ Fossil Shell Agro 10g+ Chicken Manure 50g (T3), Fossil Shell Agro 10g+ Chicken Manure 50g (T4), Calcium Silicate 50g+ Chicken Manure 50g (T5), Agricultural Lime 50g+ Biochar 50g+ Chicken Manure 50g (T6) and Control without doses, one month after the last application of the treatments, the healthy and ripe CCN-51 cocoa pods were harvested, the pods were broken by hand and the beans were taken directly to the fermenter. The fermentation method used was that of a single level wooden crate. The duration of the fermentation process was 3 days with a daily dough removal in a period of 24 hours. The drying process was carried out in 7 days placed in plastic mesh canopies exposed to the natural drying of the grains until a humidity of 7 to 8% was obtained. When the grains reached the required humidity percentage, they were stored in labelled plastic covers, separated from each treatment. Once the cocoa was fermented and dried, 100 beans were taken at random from each treatment to determine the cutting test where the physical properties of the beans were evaluated such as cob index, vean index, Shell percentage and fermentation percentage. In order to compare the results of the treatments and controls and to obtain the means between the variables, the SPSS program as used, where it was possible to determine that T3 obtained the highest values in relation to the ear index and the second highest value in the bean index and percentage of shell, while T6 obtained the highest value in the bean index and T1 the lowest and most accepted value in the percentage of shell. In the percentage of good fermentation, T4 showed the best results and T3 obtained the highest value in the percentage of medium fermentation. Regarding the sensory quality of the cocoa liquor, T4 obtained the highest value in the specific flavors in the sensory analysis, being this the best qualified followed by T1.
El biochar es un producto rico en carbono que se lo obtiene mediante la descomposición de la materia orgánica a través del proceso de pirólisis, el biochar genera respuestas positivas al ser usado como enmienda edáfica en los suelos agrícolas, mejora las propiedades fisicoquímicas del suelo y el comportamiento fisiológico de las plantas. El biochar favorece la producción y rendimientos de los cultivos y tiene un efecto positivo en el aumento en la calidad y peso de los frutos. Ecuador es considerado como el primer productor de cacao fino y de aroma con el 70% de la producción mundial, gracias a las condiciones ecogeográficas de nuestro país que permiten al cultivo expresar todas sus bondades en calidad, sabor y aroma. La existencia del cacao se remonta 2000 años atrás Centroamérica, cultivado y producido por civilizaciones como los Mayas y Aztecas, aunque existen vestigios arqueológicos de variedades del Theobroma cacao subsp. Cacao que datan más de 5000 años encontradas en la zona del litoral y Amazonía del Ecuador. Actualmente el cacao tipo Nacional se encuentra en peligro de extinción ya que está siendo reemplazado por otros materiales más productivos, entre los que destaca el híbrido clonal CCN-51, por su resistencia a plagas y enfermedades y de gran productividad, clon que junto al desarrollo de nuevas técnicas de fermentación comenzó a ser uno de los más apetecidos y valorados a nivel mundial por su calidad y aroma. El objetivo principal de este trabajo fue determinar el efecto del biochar aplicado como enmienda edáfica solo y en combinación con otras enmiendas edáficas en la calidad sensorial del cacao CCN-51. Para este trabajo se aplicaron los tratamientos en diez plantas al azar por cada bloque, esto se desarrolló en la finca “Don Hermel” perteneciente al sector de Río Negro, las dosis de los tratamientos fueron: Biochar 100g+ Gallinaza 50g (T1), Biochar 100g+ Fossil Shell Agro 5g+ Gallinaza 50g (T2), Biochar 50g+ Fossil Shell Agro 10g+ Gallinaza 50g (T3), Fossil Shell Agro 10g+ Gallinaza 50g (T4), Silicato de calcio 50g+ Gallinaza 50g (T5), Cal Agrícola 50g+ Biochar 50g+ Gallinaza 50g (T6) y Testigo sin dosis, luego de un mes de la última aplicación de los tratamientos, se cosechó las mazorcas sanas y maduras del cacao CCN-51, se realizó el quiebre de las mazorcas que fueron desganadas de forma manual, los granos fueron llevados directamente al fermentador. El método de fermentación usado fue el de cajón de madera a un solo nivel, el tiempo de duración del proceso de fermentación fue de 3 días con una remoción de masa diaria en un lapso de 24 horas. El proceso de secado se realizó en 7 días colocados en marquesinas de malla plástica expuesta al secado natural de los granos hasta obtener una humedad de 7 a 8%. Cuando los granos alcanzaron el porcentaje de humedad necesario fueron almacenados en fundas plásticas etiquetadas y separadas de cada tratamiento. Una vez fermentado y secado el cacao se tomó 100 granos al azar de cada tratamiento para determinar la prueba de corte donde se evaluó las propiedades físicas de los granos como índice de mazorca, índice de grano, porcentaje de cascarilla y porcentaje de fermentación. Para comparar los resultados de los tratamientos y testigo y poder obtener las medias entre las variables se utilizó el programa SPSS, donde se pudo determinar que el T3 obtuvo los valores más altos con relación al índice de mazorca y el segundo valor más alto en el índice de grano y porcentaje de cascarilla, en cambio el T6 obtuvo el valor más alto en el índice de grano y el T1 el valor más bajo y más aceptado en el porcentaje de cascarilla. En el porcentaje de fermentación buena el T4 fue el que mostró mejores resultados y el T3 obtuvo el valor más alto en el porcentaje de fermentación media. Con respecto a la calidad sensorial del licor de cacao, el T4 obtuvo el valor más alto en los sabores específicos en el análisis sensorial siendo este el mejor calificado seguido el T1.
Keywords: BIOCHAR; FERMENTACIÓN; SECADO; CACAO